Microstructural development and oxygen ion mobility in Sr, Ba, and Ca-doped LaAlO3 perovskites - Villas-Boas, Lucia Adriana [UNESP]; Goulart, Celso Antonio; Ferreira de Souza, Dulcina Pinatti (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2020)
Perovskite-type materials have been extensively investigated in the attempt to find new electrolyte materials for Solid Oxide Fuel Cell that work at low temperatures. Among these materials, LaAlO3 stands out for presenting considerable ionic conductivity when adequately doped. In this work, pure and Sr, Ba, and Ca-doped LaAlO3 were studied. The powders were prepared by solid state reaction. Microstructural, structural and electrical conductivity of sintered samples were analyzed by scanning electron microscopy, X-ray diffraction and impedance spectroscopy, respectively. Among the different kinds of dopants, Sr-doped sample presented the higher conductivity, for both the grain (at 800 degrees C) and total (at 800 degrees C) conductivity. In all doped samples, the total conductivity is controlled by the grain boundary, i.e., the grain boundary is more resistive than the grain, and the microstructures are heterogeneous and the degree of heterogeneity is determined by the dopant.
Keywords: electrolyte; SOFC; perovskite; lanthanum aluminate